EOSINOFIL DAN ASMA - A. Jalal, Elyusrar (Jurnal Kedokteran YARSI, 2005)
Eosinophils are often found as dominant inflammatory cells present in the airways of asthma patients, but the importance of these white blood cells has been poorly understood. The eosinophil functional activity, like immune response in general may be beneficial or harmful for the organism. They could have an important role in the disordered repair that leads to permanently impaired function of airways tissue in asthmatic. This paper is a review focused on the relationship of eosinophil and their products with asthma.